Mumps Antibody Response in Young Adults After a Third Dose of Measles-Mumps-Rubella Vaccine. (18th October 2014) - Fiebelkorn, Amy Parker; Coleman, Laura A.; Belongia, Edward A.; Freeman, Sandra K.; York, Daphne; Bi, Daoling; Zhang, Cheryl; Ngo, Laurie; Rubin, Steven
Abstract : Baseline mumps antibody titers were high-seropositive for 93.4% of subjects, low-seropositive for 5.8%, and seronegative for <1%. One month after a third measles-mumps-rubella vaccine dose, mumps titers had a modest but significant increase. One year later, titers returned to near baseline. Abstract: Background. Mumps outbreaks in populations with high 2-dose measles-mumps-rubella (MMR) vaccine coverage raise the question whether a third dose of MMR vaccine (MMR3) is needed. However, data on the immunogenicity of MMR3 are limited. We assessed mumps virus neutralizing antibody levels pre- and post-MMR3 in a nonoutbreak setting. Methods. Mumps antibody titers were assessed at baseline, 1 month, and 1 year after MMR3 in subjects aged 18–28 years. Results. At baseline, 5 of 656 (0.8%) subjects had seronegative mumps neutralizing antibody titers and 38 (5.8%) had low titers. One year post-MMR3, these numbers declined to 3 (0.5%) and 16 (2.4%), respectively. Subjects with low baseline titers were more likely to have low 1-month and 1-year titers ( R 2 = 0.81–0.87, P < .0001). Compared to baseline, geometric mean titers were significantly higher at 1 month ( P < .0001) and 1 year ( P < .01) post-MMR3; however, reverse cumulative distribution curves showed only minimal shifts in mumps titers from baseline to 1 month and 1 year. Conclusions. Very few subjects had negative or low baseline mumps titers. Nonetheless, mumps titers had modest but significant increases when measured 1 month and 1 year post-MMR3. This temporary increase in titers could decrease susceptibility to disease during outbreaks, but may have limited value for routine use in vaccinated populations.